Creating a Smart Learning Environment for English Proficient Students: Parental Involvement - Rejeki Murtiningsih Sri; Ayuningtyas Sekar; Haryadi Didit (SHS Web of Conferences)
Parental involvement is crucial in fostering a smart learning environment, particularly for enhancing English proficiency among students. This study examines the role of parents in creating such an environment and the challenges they face. Using qualitative approach, in-depth interviews were conducted with four parents of students with high English proficiency at an Islamic elementary school in Magelang, Indonesia. The findings highlight various forms of parental involvement, including English learning support, provision of learning facilities, supervision during study sessions, collaboration with schools, and mental support. The research also identifies six key challenges: teaching English at home, supporting English learning, unsupportive academic backgrounds, low parental skills, busy schedules, and managing emotions. These insights are vital for developing strategies that enhance parental involvement to create smart learning environments and ultimately improve students’ English proficiency. Implications for parents, institutions, and further research are discussed in this study.